2020
DOI: 10.1002/jsfa.10716
|View full text |Cite
|
Sign up to set email alerts
|

Foxtail millet: a potential crop to meet future demand scenario for alternative sustainable protein

Abstract: Foxtail millet (Setaria italica), an annual grass plant, produces seeds that possess health‐promoting properties owing to its unique protein composition containing a high content of essential amino acids. The mature foxtail seeds mainly consist of proline‐rich, alcohol‐soluble proteins (prolamin) called setarins, comprising about 60% of the total protein, with less content of disulfide cross‐linked proteins than with other cereal and millets. Protein fractionation schemes are an important tool and provide prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 90 publications
0
43
0
Order By: Relevance
“…Also, the millets are gluten-free and have a low glycemic index ( Muthamilarasan and Prasad, 2021 ). Foxtail millet is considered an alternative sustainable protein source compared to other cereals and millets ( Sachdev et al, 2021 ). Being a rich source of zinc and iron, the consumption of millets imparts immunity ( Kumar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the millets are gluten-free and have a low glycemic index ( Muthamilarasan and Prasad, 2021 ). Foxtail millet is considered an alternative sustainable protein source compared to other cereals and millets ( Sachdev et al, 2021 ). Being a rich source of zinc and iron, the consumption of millets imparts immunity ( Kumar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Foxtail millet contains high levels of protein and fiber [14]. The main protein fractions from foxtail millet are prolamins (up to 60% of the total protein content) and glutelins, which are rich in essential amino acids [15]. Foxtail millet has been listed among protein sources with good potential for replacing animal proteins in different types of products.…”
Section: Introductionmentioning
confidence: 99%
“…Foxtail millet has been listed among protein sources with good potential for replacing animal proteins in different types of products. It has been reported that foxtail millet proteins display bioactive effects that are promising for the efficient management of different human chronic diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…The publishments of many foxtail millet cultivars genome sequences and the discovery of model C4 plant species foxtail millet mutant xiaomi, provided the enormous convenience for the research of foxtail millet (Bennetzen et al 2012, Zhang et al 2012, Yang et al 2020. Hulled grain of foxtail millet is rich in nutrients including essential amino acids, fatty acids, minerals and vitamines (Sachdev et al 2021). Compared to the major crops, foxtail millet is rich of folates.…”
Section: Introductionmentioning
confidence: 99%